Partial Discharge Localization Method for Individual Operation Based on Double Antenna Array - Songyuan Li, Bowen Guo, Qinghua Tang, Nan Li, Penfei Li (Forest Chemicals Review)
To improve the efficiency and accuracy of partial discharge (PD) location in substation, a new method for individual operation is proposed based on ultra-high frequency (UHF) method. In specialty, two UHF sensors are used to build antenna array for measuring the azimuth of PD source, the efficiency and accuracy were improved by studying the accuracy influencing factors and weights of the PD localization model through the sensitivity analysis method. And then, the method is simplified, and the system error, influencing factors, and weight of the simplified method are analyzed. The PD location device for individual operation is developed and tested in a 500 kV substation. The result shows that the method has high accuracy for measuring the azimuth, and the error is smaller as the angle between PD source and antenna array is closer to 90̊, and the accuracy can be further improved by adjusting the angle of the antenna array and improving the sampling rate. The study provides important significance for improving the accuracy and efficiency of PD localization in substation.